2018
DOI: 10.1590/s1678-9946201860046
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on the HPV vaccine among university students

Abstract: The objective is to evaluate knowledge on HPV vaccine and its use among university students. This is a cross-sectional study with 301 participants, of which 202 medical students from UERJ and UNIFESO (101 freshmen = M1 and 101 from the 6th year = M2) and 99 UERJ literature students (50 freshmen = L1 and 49 of the last year = L2). Information was obtained by questionnaires. Input and statistical analysis were carried out with the EPI-INFO 3.5.2 Program. Results showed that, among medical students, 21% of M1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
3
9
0
4
Order By: Relevance
“…Furthermore, among the participants in this study, the vaccination status was not significantly related to the level of medical training, which was similar to the findings of other authors 9 , 22 that a higher level of knowledge did not reflect in higher vaccination rates. On the other hand, Afonso et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, among the participants in this study, the vaccination status was not significantly related to the level of medical training, which was similar to the findings of other authors 9 , 22 that a higher level of knowledge did not reflect in higher vaccination rates. On the other hand, Afonso et al .…”
Section: Discussionsupporting
confidence: 90%
“…This study carried out with undergraduate medical students shows significant differences in the HPV vaccination status according to sex, sexual behavior and source of information about the vaccine. The vaccination rates among female medical students in Brasilia and Rio de Janeiro were comparable, but they were much lower than those found in Glasgow or Rochester 4 , 8 , 9 . One reason for the lower vaccination rate is the recent start (2014) 5 of the national program of immunization against HPV in Brazil, in comparison with the initiation of the UK (2008) 4 or the US (2006) 8 HPV vaccination.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In that manner, we proved that subjects involved in medical studies or those that attended medical high school had the highest knowledge about CC. Other authors also confirmed that medical students are highly educated on this matter [27,28], which is understandable and very commendable, as they represent the leaders of further education of the general public about CC. In accordance with the previous interpretation, the results of another Serbian study showed that both students of a secondary medical school and midwives who had finished at that same school had significantly better knowledge than patients [29].…”
Section: Discussionmentioning
confidence: 72%
“…Um dos grandes desafios para a saúde pública é informar a população sobre o HPV e desenvolver formas precisas de comunicação através da mídia, igrejas, escolas e organizações não governamentais (MONTEIRO et al, 2018). Ao considerar a prevalência de HPV e sua estreita relação ao câncer de colo do útero e as baixas coberturas vacinais, este estudo é de grande relevância pública, visto que, estabelecer estratégias exige uma análise da cobertura vacinal detalhada.…”
Section: Introductionunclassified